2019
DOI: 10.3389/fncel.2019.00003
|View full text |Cite
|
Sign up to set email alerts
|

Connexin and Pannexin-Based Channels in Oligodendrocytes: Implications in Brain Health and Disease

Abstract: Oligodendrocytes are the myelin forming cells in the central nervous system (CNS). In addition to this main physiological function, these cells play key roles by providing energy substrates to neurons as well as information required to sustain proper synaptic transmission and plasticity at the CNS. The latter requires a fine coordinated intercellular communication with neurons and other glial cell types, including astrocytes. In mammals, tissue synchronization is mainly mediated by connexins and pannexins, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 116 publications
0
15
0
Order By: Relevance
“…These studies revealed that the brain transcriptomes of Cx43KO mouse and Cx32KO mouse were both 83% altered with respect to the wildtype counterpart, whereas their similarity to the brain of Cx36KO mouse were respectively 12% and 11% [12]. Since astrocytes and oligodendrocytes form heterocellular gap junction channels with each other [14][15][16], but none with neurons has been yet reported in the mouse brain (after our knowledge), these results suggested "panglial transcriptomic continuity". By transcriptomic continuity we understand that transcriptomic changes in one cell type has consequences in another cell type.…”
Section: Introductionmentioning
confidence: 78%
“…These studies revealed that the brain transcriptomes of Cx43KO mouse and Cx32KO mouse were both 83% altered with respect to the wildtype counterpart, whereas their similarity to the brain of Cx36KO mouse were respectively 12% and 11% [12]. Since astrocytes and oligodendrocytes form heterocellular gap junction channels with each other [14][15][16], but none with neurons has been yet reported in the mouse brain (after our knowledge), these results suggested "panglial transcriptomic continuity". By transcriptomic continuity we understand that transcriptomic changes in one cell type has consequences in another cell type.…”
Section: Introductionmentioning
confidence: 78%
“…They mainly contribute to conduction inside neuronal circuits, but they also participate in metabolic supply and ion buffering [81,82]. Oligodendrocytes mainly express Cx29, Cx32, and Cx47; through these connections, they form channels with astrocytes and with themselves (heterotypic unions of Cx30 and Cx32, and of Cx43 and Cx47) [7,83]. These functional unions of Cxs even participate in the release of gliotransmitters, although it is not clear if oligodendrocytes have the necessary molecular machinery to fulfill this task [84].…”
Section: Connexins-based Hemichannels/channels and Neuroinflammationmentioning
confidence: 99%
“…These intercellular interactions between competing oligodendroglial cells influence the number and length of myelin internodes as well as the initiation of differentiation (54,55). Oligodendrocytes are also coupled to astrocytes through heterologous gap junctions such as Cx32/Cx30 and Cx47/Cx43 (56). Disruption of oligodendrocytes from each other and from astrocytes, i.e.…”
Section: Discussionmentioning
confidence: 99%